2014
DOI: 10.1007/s10120-014-0390-y
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Ephrin A2 receptors in cancer stromal cells is a prognostic factor for the relapse of gastric cancer

Abstract: Background Microenvironments control cancer growth and progression. We explored the prognostic impact of stromal reaction and cancer stromal cells on relapse risk and survival after curative gastrectomy in gastric cancer patients. Methods Tissue samples were obtained from 107 patients with gastric adenocarcinoma who underwent curative (R0) gastrectomy. Primary stromal cells isolated from gastric cancer tissue (GCSC) and normal gastric tissue (Gastric stromal cell: GSC) in each patient were cultured and subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…This was in line with recent findings based on studies focused on the oncogenic role of EphA2 in CRC and other tumors (31,34,37). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This was in line with recent findings based on studies focused on the oncogenic role of EphA2 in CRC and other tumors (31,34,37). …”
Section: Discussionsupporting
confidence: 92%
“…Differently than normal tissue, adenocarcinoma displayed a highly heterogeneous and not gradient-disposed staining for both EphB2 and EphA2 proteins and it was enriched in EphA2 high cell fractions also showed in the cytofluorimetric analysis. The overexpression of EphA2 has been recently reported in different kinds of solid tumors, included the colon (31,34–37). Conversely, a reduction of EphB2 high cell subpopulation was observed in adenocarcinoma.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that tyrosine kinase Src can induce phosphorylation and activation of YAP. 31 We and others have previously reported that EphA2 overexpression is associated with poor prognosis for GC patients and promotes the EMT and invasion of GC cells through the Wnt/β-catenin pathway. 28 Altogether, it seems to be that except few cases, serine/threonine kinases phosphorylate YAP, leading to cytoplasmic retention, degradation and inactivation of YAP, while tyrosine kinase phosphorylate YAP, resulting in stabilization, nuclear translocation and activation of YAP.…”
Section: Discussionmentioning
confidence: 81%
“…30 Overexpression of Ephrin A2 receptors in cancer stromal cells is a prognostic factor for the relapse of gastric cancer. 31 We and others have previously reported that EphA2 overexpression is associated with poor prognosis for GC patients and promotes the EMT and invasion of GC cells through the Wnt/β-catenin pathway. 8,11,12 In present study, we further confirm the role of EphA2 in GC growth and development, and find that the regulation of YAP by EphA2 is one of the major mechanisms underlying EphA2-driven GC development, progression and therapy resistance.…”
Section: Discussionmentioning
confidence: 81%
“…While the role of these genes in RMS remains to be specifically defined, majority of them have been implicated in cancer. EPHA2 receptor overexpression in gastric cancer stromal cells is a prognostic factor for relapse (23). It also promotes tumor cell proliferation and motility in non-small cell lung cancer (24); and increases infiltrative capacity of glioma stem cells in glioblastoma multiforme models (25).…”
Section: Discussionmentioning
confidence: 99%